Chronic Traumatic Encephalopathy Within an Amyotrophic Lateral Sclerosis Brain Bank Cohort. Issue 12 (9th October 2018) - Walt, Gabriel S; Burris, Hannah M; Brady, Christopher B; Spencer, Keith R; Alvarez, Victor E; Huber, Bertrand R; Guilderson, Latease; Abdul Rauf, Nazifa; Collins, Derek; Singh, Tarnjit; Mathias, Rebecca; Averill, James G; et al.
Abstract: Chronic traumatic encephalopathy (CTE) is a progressive neurodegenerative disorder linked to repetitive head impacts and has been associated with amyotrophic lateral sclerosis (ALS), a fatal, degenerative neuromuscular disorder. The Department of Veterans Affairs Biorepository Brain Bank (VABBB) is a tissue repository that collects antemortem disease progression data and postmortem central nervous system tissue from veterans with ALS. We set out to determine the frequency of co-morbid ALS and CTE in the VABBB cohort and to characterize the clinical, genetic, and pathological distinctions between participants with ALS only and those with both ALS and CTE (ALS+CTE). Of 155 participants, 9 (5.8%) had neuropathologically confirmed ALS+CTE. Participants with ALS+CTE were more likely to have a history of traumatic brain injury (p < 0.001), served during the first Persian Gulf War (p < 0.05), and to have more severe tau pathology within the frontal cortex and spinal cord (p < 0.05). The most common exposures to head impacts included contact sports (n = 5) and military service (n = 2). Clinically, participants with ALS+CTE were more likely to have bulbar onset ALS (p = 0.006), behavioral changes (p = 0.002), and/or mood changes (p < 0.001). Overall, compared with ALS in isolation, comorbid ALS+CTE is associated with a history of TBI and has a distinct clinical and pathological presentation.